Designing a Sustainable Business Model for Cattle Manure-Based Organic Fertilizer - Rizky Oktavian; Sri Mulatsih; Supriyanto Supriyanto (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
The cattle farming industry in Indonesia has experienced significant growth, with the population increasing from 14.8 million head (2014) to 18.8 million head (2023). This industry generates approximately 137.2 million tons of waste annually, yet only 30% is processed into value-added products. This research aims to design a sustainable business model for converting cattle farm waste into organic fertilizer. The study employs a qualitative approach with case studies across three scales of cattle farming operations in Bogor and Cianjur Regencies. Analysis was conducted using the Business Model Canvas (BMC), Value Chain Analysis, and PESTEL framework. Results identify four key driving factors in the cattle waste processing business: infrastructure and technology (GM=4.64-5.00), HR management (GM=4.00-5.00), procurement (GM=4.47-5.00), and inbound logistics (GM=4.47-5.00). A Central Processing Unit (CPU) model was designed with a capacity of 25 tons of cattle waste per day. Feasibility analysis indicates an investment requirement of IDR 11.5 billion, yielding a 12-month payback period, NPV of IDR 59.39 billion, and IRR of 100.3%. The model demonstrates economic sustainability through multiple revenue streams with projected annual revenue of IDR 21.24 billion, positive environmental impact through 60% emission reduction, and social contribution by creating 23-25 new jobs.